“Placebo by Proxy” and “Nocebo by Proxy” in Children: A Review of Parents' Role in Treatment Outcomes - Czerniak, Efrat; Oberlander, Tim F.; Weimer, Katja; Kossowsky, Joe; Enck, Paul (Frontiers in Psychiatry, 2020)
The “placebo (effect) by proxy” (PbP) concept, introduced by Grelotti and Kaptchuk in 2011, describes a positive effect of a patient’s treatment on persons in their surrounding such as family members or healthcare providers, who feel better because the patient is being treated. The PbP effect is a complex dynamic phenomenon which attempts to explain a change in treatment outcome arising from an interaction between a patient and an effect from proxies such as parents, caregivers, physicians or even the media. By extension the effect of the proxy can also have a negative or adverse effect whereby a proxy feels worse when a patient is treated, giving rise to the possibility of a “nocebo (effect) by proxy” (NbP), and by extension can influence a patient’s treatment response. While this has yet to be systematically investigated, such an effect could occur when a proxy observes that a treatment is ineffective or is perceived as causing adverse effects leading the patient to experience side effects. In this narrative review, we take these definitions one step further to include the impact of PbP/NbP as they transform to affect the treatment outcome for the patient or child being treated, not just the people surrounding the individual being treated. Following a systematic search of literature on the subject using the Journal of Interdisciplinary Placebo Studies (JIPS) database (https://jips.online) and PubMed (NCBI) resulted in very few relevant studies, especially in children. The effect of PbP per se has been studied in parents and their children for temper tantrums, acupuncture for postoperative symptoms, as well as for neuroprotection in very preterm-born infants. This paper will review the PbP/NbP concepts, show evidence for its presence in children’s treatment outcome and introduce clinical implications. We will also offer suggestions for future research to further our understanding of the role of the proxy in promoting or distracting from treatment benefit in children. Increasing an appreciation of the PbP and NbP phenomena and the role of the proxy in children’s treatment should improve research study design and ultimately harness them to improve clinical child healthcare.